Combination of sugar-sweetened beverage consumption, screen-based sedentary time, and sleep duration and their association with South Korean adolescents' mental health - Ra, Jin Suk (Frontiers in Public Health, 2024)
This study examines the combinations of sugar-sweetened beverage (SSB) consumption, screenbased sedentary time, and sleep duration and their association with adolescents' depressive symptoms and suicidal ideation. This research followed a cross-sectional study design. Secondary data analysis was conducted on the data collected from 21,046 high school students who had participated in the 17th Korea Youth Risk Behavior Web-Based Survey in 2021. A complex sampling analysis, including descriptive and logistic regression analyses, was conducted in SPSS Statistics 26.0. The combination of low SSB consumption, excessive screen-based sedentary time, and short sleep duration was associated with an increase in depressive symptoms. In addition, a combination of medium/high SSB consumption, appropriate/excessive screen-based sedentary time, and short sleep duration was associated with an increase in depressive symptoms. Finally, the combination of high SSB consumption, excessive screen-based sedentary time, and short sleep duration was associated with an increase in suicidal ideation. The findings demonstrate that healthcare providers should develop and conduct family-and school-based programs to restrict SSB consumption, screen-based sedentary behaviors, and sleep duration to improve adolescents' mental health.